EDUKASI GIZI DENGAN MEDIA BOOKLET TERHADAP TINGKAT PENGETAHUAN, ASUPAN KALSIUM DAN AKTIVITAS FISIK UNTUK MENCEGAH OSTEOPOROSIS PADA LANSIA - Nurul Hidayah; Diniyah Kholidah; Annasari Mustofa (Jurnal Pendidikan Kesehatan, 2019)
Osteoporosis in the elderly can occur due to a variety of factors, including physical activity and less due to an intake of calcium from foods that are low. Efforts that can be made as prevention is to increase knowledge through booklets and familiarize behaves live a healthy life, i.e., consuming foods high in calcium and physical activity or exercise routine. The purpose of this research is to know the influence of nutrition education with the media booklet against the level of knowledge, calcium intake and physical activity to prevent osteoporosis in the elderly in the RSIA Puri Malang. Research methods using pre experimental design with one group pretest posttest design. Sampling by means of purposive sampling obtained a sample of 26 respondents research with attention to inclusion and exclusion criteria.The difference in the average level of knowledge of respondents about calcium intake and physical activity before and after being given the nutritional education of 15.77 points that mean there is a change in the knowledge of the respondent. Statistical tests paired sample t test shows there is a significant difference. The difference in the average intake of calcium the respondent before and after given the nutritional education of 52.95 mg which means there is a change in the intake of calcium of the respondents. Statistical tests paired sample t test shows there is a significant difference. The difference in average physical activity the respondent before and after nutrition education is given in the amount of minus 0.04 points which means there is no change in the physical activity of respondents. Statistical tests paired sample t test showed there was no significant difference. Nutrition education needs to be done on an ongoing basis by providing substantial material about calcium intake needs for elderly accompanied sample menu of foods that can be applied, providing the motivation so that the elderly routinely follow gymnastics elderly and doing sport itself as well as the need to do further research to look at the description of food intake based on the respondent eating habits daily.